2001
DOI: 10.1093/clinchem/47.9.1627
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Porphobilinogen in Urine by Stable-Isotope Dilution Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Background: Measurement of porphobilinogen (PBG) is useful in the diagnosis of the acute neurologic porphyrias. Currently used colorimetric assays lack analytical and clinical sensitivity and specificity. Methods: We developed a liquid chromatography-electrospray tandem mass spectrometry (LC-MS/MS) method for the measurement of PBG in 1 mL of urine, using 5-(aminoethyl)-4-(carboxymethyl) 1H-2,4-[13C]pyrolle-3-propanoic acid ([2,4-13C]PBG; 2.75 μg) as internal standard. After solid-phase extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…ALA and PBG are highly polar compounds and are not sufficiently retained using conventional reversed-phase chromatography. Such methods are susceptible to significant matrix effects because of the insufficient retention of ALA and PBG (Ford et al, 2001). A method using a nonvolatile ion-pairing reagent (Crowne et al, 1981) has been reported, but such buffers are incompatible with mass spectrometric operation.…”
mentioning
confidence: 99%
“…ALA and PBG are highly polar compounds and are not sufficiently retained using conventional reversed-phase chromatography. Such methods are susceptible to significant matrix effects because of the insufficient retention of ALA and PBG (Ford et al, 2001). A method using a nonvolatile ion-pairing reagent (Crowne et al, 1981) has been reported, but such buffers are incompatible with mass spectrometric operation.…”
mentioning
confidence: 99%
“…(c)). Taking into account that the unknown compound could be related to PBG and that PBG is mainly ionised in positive mode as [M + H−NH 3 ] + , a more detailed study was necessary for establishing the molecular formula of the species.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] In the case of AIP, several LC-MS/MS-based methods have been reported for the target quantification of PBG and ALA in human urine. [14][15][16][17] Additionally, both GC-MS and LC-MS/MS have been used in the evaluation of hormonal and metabolic imbalances in AIP patients. [18,19] Inspection of the urine of AIP patients in our centre by LC-MS/MS leads to the observation of an unidentified chromatographic peak that appeared in all urines from patients with porphyria, whereas its presence was undetectable in all control samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A stable-isotope dilution HPLC-ESI-MS/MS method has been described for the quantitation of PBG in urine using 2,4-13 C 2 -PBG as internal standard (IS) with a calibration range from 0.05 to 3.0 mg/L (0.22-13 mmol/L; Ford et al, 2001). PBG was extracted using solid-phase extraction and separated using a Supelcosil LC-18 column with a mobile phase of acetonitrile and formic acid in water.…”
Section: Liquid Chromatography-mass Spectrometry Of Ala and Pbgmentioning
confidence: 99%